Shergar discover the heart of a champion - Rourke, Mickey; Holm, Ian.; Warner, David; Connolly, Andrew; Sterling Home Video (Fort Mill, S.C. : Sterling Home Video, 1999)
Based on the true story of Shergar, Ireland's most decorated thoroughbred who was kidnapped by IRA terrorists and held for a $2 million ransom.
"Based on a true story." -- Container.
Ian Holm, Mickey Rourke, David Warner, Andrew Connolly.
VHS.